Antibiotic resistance rate of the Methicillin Resistant Staphylococcus aureus isolated from a university affiliated hospital in North Cyprus (Bangladesh Journal of Medical Science, 2022)
Background: Over the past 20 years, studies have indicated that the increasing spread of methicillinresistant Staphylococcus aureus (MRSA) demonstrates the need for adequate information about their epidemiology. This study was conducted in order to investigate the resistance rate of MRSA which were isolated from the Near East University (NEU) Hospital, North Cyprus.Methods: MRSA was isolated and identified by using selective media and the Phoenix BD 100 system (software version 6.01A) was used for antimicrobial susceptibility testing and identification. The antimicrobial susceptibility results were determined according to the Clinical and Laboratory Standarts Institute (CLSI) and the resistance rates of MRSA isolates to antibiotics were examined retrospectively.Results: The highest number of samples were from the departments of chest disease (24%) followed by dermatology (21.3%) and cardiology (18.7%). Out of 75 MRSA strains,; 29.7% from blood, 25.3% from wound, 14.7% from nasal swabs, 10.7% from aspiration fluids, 9.3% from sputum, 6.7% were from urine, 4.0% from IV catheters culture samples. All strains of MRSA were 94.7% sensitive to vancomycin and teicoplanin.Conclusions: The obtained results revealed that preventative measures should be implemented in order to minimize the bacterial resistance to antibiotics.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 101-104